The Effect of Solution Heat Treatment Temperature on Phase Transformations, Microstructure and Properties of Ti-25Ta-xZr Alloys Used as a Biomaterial - Kuroda, Pedro Akira Bazaglia [UNESP] (2020)
This paper describes a study of the effect of solution heat treatment temperature (500, 750 and 1000 °C) on the phase transformations, microstructure, microhardness and Young’s modulus of Ti-25Ta-xZr alloys, aimed at biomedical applications. The Ti-25Ta-xZr alloys ingots were melted in an arc furnace with five different compositions (x = 0, 10, 20 30 and 40 wt.%) in order to produce samples with α″, β + α″ and β phase. The results showed that both the microstructure and mechanical properties of the studied alloys can be tailored according to the temperatures used for solution in the Ti-25Ta-xZr system. Usually, higher solution heat treatment temperatures increase hardness due to the higher phase stabilization in single-phase alloys, while in the α″ + β alloys or predominantly β, hardness decreases due to the suppression of phase α″. However, the elastic modulus of the alloys decreases when solution heat treatment is performed at 1000 °C. In general, solution heat treatment performed at higher temperatures stabilizes more the β phase, optimizing the lower modulus of the alloys.